2020
DOI: 10.1080/23311886.2020.1753487
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ethnic culture in choosing the learning type of ethnic minorities: Evidence from Northwest of Vietnam

Abstract: One of the concerns in improving the quality of minority education in multicultural nations is how to choose the appropriate types of learning for different ethnic groups, especially when such decision can be constrained their cultural diversity. This paper aims to analyze the effect of cultural differences on selecting types of learning for ethnic minorities; thus, recommending some ethic-specific policies to better utilize the manpower resources in the Northwest region of Vietnam. Questionnaires were employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Burning aside, it was commonly reported that skeletal elements were covered with red ocher, for example, ocher was noted on burials at Hang Con Moong (Hoàng and Nguyễn 1976), Mái đá Làng Vanh (Colani 1929), Mái đá Triềng Xén (Colani 1927b) and Mái đá Điều (Nguyễn 1994b). The use of ocher was also mentioned by Nguyễn (1994a) in his review paper at Hang Con Moong, Hang Muối, and Hang Dắng. Hang Muối 1, the relatively shallow supine-extended burial of unclear date (but likely Neolithic), was described as resting on a bed of ocher (Phạm et al 1967).…”
Section: While We Have Not Undertaken An Exhaustive Review Of Mainlan...mentioning
confidence: 95%
See 3 more Smart Citations
“…Burning aside, it was commonly reported that skeletal elements were covered with red ocher, for example, ocher was noted on burials at Hang Con Moong (Hoàng and Nguyễn 1976), Mái đá Làng Vanh (Colani 1929), Mái đá Triềng Xén (Colani 1927b) and Mái đá Điều (Nguyễn 1994b). The use of ocher was also mentioned by Nguyễn (1994a) in his review paper at Hang Con Moong, Hang Muối, and Hang Dắng. Hang Muối 1, the relatively shallow supine-extended burial of unclear date (but likely Neolithic), was described as resting on a bed of ocher (Phạm et al 1967).…”
Section: While We Have Not Undertaken An Exhaustive Review Of Mainlan...mentioning
confidence: 95%
“…The cultural layer, which is 1 m deep, revealed one burial at a depth of 0.55 m (Hoàng 1985(Hoàng , 1989. This individual was represented by cranial and postcranial fragments and the cranial fragments were reportedly burned (Nguyễn 1994a). The remains were identified as an old male (Hoàng 1985(Hoàng , 1989Nguyễn 1991Nguyễn , 1994a who was lying on his side, with his lower limbs flexed (Nguyễn 1994a) and head oriented to the northwest.…”
Section: Hòabìnhian Burial Practices độNg Canmentioning
confidence: 99%
See 2 more Smart Citations